The Correlational Analysis of Motivation and Productivity of Librarians in Public Universities in Nigeria - AbdulazeezYaya, Japheth; EurielUzohue, Chioma; Akintayo, Oluseyi A. (IJRDO- Journal of Educational Research, 2016)
This study investigated the relationship between motivation and productivity of librarians in Nigerian public universities. A correlational survey research design was adopted. The study population consisted of 1,254 librarians in public university libraries in Nigeria, from which 923 were selected using simple random sampling. The research instrument used was a self-developed questionnaire. The study revealed a significant relationship between motivation and productivity (r = 0.035, P < 0.05) of librarians in public university libraries in Nigeria. It concluded that contrary to general belief, motivation and productivity levels of librarians in university libraries were high. It is recommended that university library management should continue to promote values such as improved employee recognition, good leadership style and improved employees’ motivational programmes that would increase productivity of its workforce.